Efficacy of a single ultrasound-guided injection for the treatment of hip osteoarthritis. Issue 1 (10th November 2010) - Atchia, Ismaël; Kane, David; Reed, Mike R; Isaacs, John D; Birrell, Fraser
Abstract : Background: Intra-articular injection is effective for osteoarthritis, but the best single injection strategy is not known, nor are there established predictors of response. The objectives of this study were to assess and predict response to a single ultrasound-guided injection in moderate to severe hip osteoarthritis. Methods: 77 hip osteoarthritis patients entered a prospective, randomised controlled trial, randomised to one of four groups: standard care (no injection); normal saline; non-animal stabilised hyaluronic acid (durolane) or methylprednisolone acetate (depomedrone). Main: Outcome Measures Numerical rating scale (NRS 0–10) 'worst pain', Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain/function. Potential predictors of response (including radiographic severity, ultrasound synovitis and baseline symptom severity) were examined using univariate logistic regression analysis and Fisher's exact test. Results: NRS pain, WOMAC pain and function improved significantly for the steroid arm alone. Effect sizes at week 1 were striking: NRS pain 1.5, WOMAC pain 1.9 and WOMAC function 1.3. Outcome Measures in Rheumatoid Arthritis Clinical Trials—Osteoarthritis Research Society responder criteria identified 22 responders (intention-to-treat): steroid 14 (74%; number needed to treat, two); saline, four (21%); durolane, two (11%); and no injection, two (10%; χ 2 test between groups, p<0.001). Corticosteroid arm response was maintained over 8 weeks (summary measures analysis of variance, p<0.002 for NRS pain). Synovitis was a significant predictor of response at weeks 4 and 8 (p<0.05, Fisher's exact test; week 4 OR 16.7, 95% CI 1.4 to 204). Conclusions: Ultrasound-guided corticosteroid injections are highly efficacious; furthermore synovitis on ultrasound is a biomarker of response to injection.